2011
DOI: 10.1111/j.1365-2893.2011.01509.x
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment HBeAg level and an early decrease in HBeAg level predict virologic response to entecavir treatment for HBeAg‐positive chronic hepatitis B

Abstract: There are few reports on hepatitis B e antigen (HBeAg) titres during nucleos(t)ide analogues treatment. We investigated the changes in HBeAg levels in patients treated with entecavir and the usefulness of HBeAg quantification for predicting antiviral response. Ninety-five consecutive HBeAg-positive patients treated with entecavir for more than 48 weeks were enrolled. Serum levels of hepatitis B surface antigen (HBsAg), HBeAg and HBV DNA were assessed at 4-week intervals to week 24 and thereafter at 12-week int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…These results were consistent with a recent study showing that a 24-month TDF therapy induced satisfactory CVR (96.6%) in 29 NA failure patients. 10 Although it was considered that early serum HBsAg or HBeAg drop was a predictor of sustained virological response to PEG IFN and NA, 23,24 application of TDF in an NA therapy failure patient or new HBV infection patient needs further studies to identify its antiviral efficacy and prediction. In this study, HBsAg values were decreased, while CVR and ALT normalization rates were increased in all patients during the TDF therapy.…”
Section: Etailed Demographics Of All Includedmentioning
confidence: 99%
“…These results were consistent with a recent study showing that a 24-month TDF therapy induced satisfactory CVR (96.6%) in 29 NA failure patients. 10 Although it was considered that early serum HBsAg or HBeAg drop was a predictor of sustained virological response to PEG IFN and NA, 23,24 application of TDF in an NA therapy failure patient or new HBV infection patient needs further studies to identify its antiviral efficacy and prediction. In this study, HBsAg values were decreased, while CVR and ALT normalization rates were increased in all patients during the TDF therapy.…”
Section: Etailed Demographics Of All Includedmentioning
confidence: 99%
“…However, other studies showed that pre-treatment serum HBeAg was associated with HBeAg SC during ETV treatment[10,12]. The inconsistent results may due to that treatment period was relatively short or HBeAg was detected semi-quantitatively in the latter’s studies[10,12].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies tried to investigate the value of an early on-treatment change of HBV markers such as HBeAg in predicting VR to NAs therapy. A study presented that the HBeAg titer decreased by 1 lg PEIU/mL at 12-wk predicted VR (HBV DNA < 20 IU/mL) after 48-wk entecavir (ETV) therapy with a sensitivity, specificity, PPV, NPV of 67.6%, 87.9%, 86.2% and 70.7%, respectively[10]. However, the predictive value of HBeAg titer and its declined value at 12-wk for a long-term treatment response (≥ 2 years) was not reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations